Therapeutic potential of Cinnamomum burmannii bark extract in reducing Malondialdehyde (MDA) levels in MSG-induced wistar rats: a preclinical study - Dina Afrianti; Wahyudi; Ririh Jatmi Wikandari; Rodhi Hartono; Erisa Febriyani; Egy Sunanda Putra (Jurnal Teknologi Laboratorium)
Increased consumption of monosodium glutamate (MSG) is associated with various health risks, including cardiovascular and neurological disorders. MSG triggers an increase in reactive oxygen species (ROS), the end product of lipid peroxidation produced when ROS increases is Malondialdehyde (MDA), On the other hand, interleukin 10 (IL-10) reduces the inflammatory effects in infectious conditions that can cause potential tissue damage. This study investigated the effect of cinnamon bark extract (Cinnamomum burmannii) on MDA and IL-10 levels in MSG-induced Wistar rats. Experiment with Post test only control group design was conducted. The number of samples was 24 male Wistar rats divided into 4 groups. KN healthy rats, K (+) rats were only induced by MSG, P1 rats were induced by MSG and given cinnamon bark extract at a dose of 100 mg, P2 rats were induced by MSG and given cinnamon bark extract at a dose of 200 mg. The average results showed a decrease in MDA levels after 14 days of treatment, one-way ANOVA test p = 0.001 (p <0.05) showed a significant difference in MDA levels KN 2.37 mg/ml ± 0.14, K+ 2.47 mg/ml ± 0.24, P1 2.32 mg/ml ± 0.20, and P2 0.84 mg/ml ± 1.07. Meanwhile, the average IL-10 levels showed no significant difference with one-way Anova test p = 0.127 (p <0.05) in the KN group, IL-10 levels were 93.25 pg / ml ± 25.01, K (+) 112.89 pg / ml ± 43.89, P1 69.48 pg / ml ± 12.83 and P2 93.29 pg / ml ± 12.11. Administration of cinnamon bark extract can reduce MDA levels in rats induced by MSG, but has no significant effect on IL-10 levels.